Feasibility of Backward Compatible MIMO Broadcasting: Issues in SISO-MIMO Coexistence - Kang, Jinkyu; Park, Sung-Ik; Jung, Hoiyoon; Hur, Namho; Ahn, Sungjun (IEEE transactions on broadcasting, 2023)
This paper introduces the application of backward compatible (B-Comp) MIMO for simultaneously supporting inter-tower communications network (ITCN) and legacy digital television (DTV) service. In B-Comp MIMO systems, SISO and MIMO broadcasting are overlaid on the same frequency, where the SISO transmission is subject to compliance with legacy system protocol. In this work, the several configurations of B-Comp MIMO are proposed in terms of physical layer multiplexing (e.g., layered or time-division multiplexing) and antenna assignment in legacy transmission, and accordingly, system-specific issues on each configuration affecting the performance degradation or practical realization are discovered. Moreover, the spectral efficiency performance of each configuration is derived and analyzed under the system-specific issues in terms of the achievable throughput for ITCN while guaranteeing the legacy service's requirements. Through such investigations with qualitative inspections, theoretic analysis, and numerical simulations, practical observations are modeled in a theoretic framework, and performance-objected tradeoffs are explicitly revealed to allow insightful decisions to answer which configuration is optimal for each use case. Lastly, the performance penalties from pilot-related limitations are delved into and hence a comprehensive inspection is allowed in a practical view.